2023
DOI: 10.1021/acsmacrolett.3c00345
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Degradation for Polydisulfides: Main Chain Scission, Self-Immolation, Or Chain Transfer Depolymerization

Abstract: Organic polydisulfides hold immense potential for the design of recyclable materials. Of these, polymers based on lipoic acid are attractive, as they are based on a natural, renewable resource. Herein, we demonstrate that reductive degradation of lipoic acid polydisulfides is a rapid process whereby the quantity of added initiator relative to the polymer content defines the mechanism of polymer degradation, through the main chain scission, self-immolation, or "chain transfer" depolymerization. The latter mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…2D). Notably, PLA is susceptible to reduction and depolymerization, 47 making it a promising candidate for non-invasive drug delivery. 48 Some studies have shown that the structures of PLA depend on the nucleophilicity of the initiators.…”
Section: Rop Polymerization Of La Moleculesmentioning
confidence: 99%
“…2D). Notably, PLA is susceptible to reduction and depolymerization, 47 making it a promising candidate for non-invasive drug delivery. 48 Some studies have shown that the structures of PLA depend on the nucleophilicity of the initiators.…”
Section: Rop Polymerization Of La Moleculesmentioning
confidence: 99%
“…Disulfide bonds are known to be easily activated by light or heat, promoting homolytic bond cleavage or metathesis reactions without an external catalyst, 107,109,124 although catalysts are often employed to accelerate reaction kinetics. Polydisulfides formed from the ROP of strained cyclic disulfides undergo CRM 125,126 via a variety of mechanisms including anionic-, 127,128 cationic-, 129,130 and radical-mediated 131,132 pathways (Figure 7). A potential disadvantage is that the efficiency of CRM can be highly dependent upon reaction conditions leading to a wide-range of monomer recovery ($20-70%) due to complex depolymerization processes proceeding via mixed mechanisms such as chain-scission or self-immolation which can both be influenced by chain-transfer events.…”
Section: Chemistry Of Dcps Displaying Closed-loop Recyclabilitymentioning
confidence: 99%
“…A potential disadvantage is that the efficiency of CRM can be highly dependent upon reaction conditions leading to a wide-range of monomer recovery ($20-70%) due to complex depolymerization processes proceeding via mixed mechanisms such as chain-scission or self-immolation which can both be influenced by chain-transfer events. 125 Nevertheless, polydisulfides feature synthetic simplicity coupled with functional complexity [133][134][135] via versatile architectural and structural adjustments, and thus can afford practical polymeric materials such as highperformance degradable adhesives. 136 Polythioesters 137 that are synthesized from the ROP of cyclic thiolactones are another class of highly dynamic DCPs that can be efficiently depolymerized (>90% monomer recovery) under mild conditions, 138 and they also feature an unusual set of performance-advantaged properties which are comparable to polymer composites such as high thermal stability, crystallinity, strength, and ductility.…”
Section: Chemistry Of Dcps Displaying Closed-loop Recyclabilitymentioning
confidence: 99%
See 1 more Smart Citation